2006
DOI: 10.4049/jimmunol.176.4.2625
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Cytomegalovirus-Specific Memory Responses in the Lung Allograft and Blood following Primary Infection in Lung Transplant Recipients

Abstract: Primary CMV infection in lung transplant recipients (LTRs) is associated with increased mortality. We studied 22 donor CMV-positive, recipient-negative (D+R−) LTRs for the development of posttransplant CMV-specific immunity. We found that 13 of 22 D+R− LTRs (59.1%) seroconverted (CMV IgG Ab+). Using pooled peptides of the immunodominant CMV Ags pp65 and IE1, we detected CMV-specific CD8+IFN-γ+ T cells in the PBMC of 90% of seroconverted individuals following primary infection by intracellular cytokine staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 48 publications
4
46
1
1
Order By: Relevance
“…We have also demonstrated that CMV-specific CD8 + T cells in the BAL were no more differentiated than those in the blood, suggesting that activated CD8 + T cells were not being redistributed to and sequestered at the site of active infection. Similarly, McDyer and colleagues in a smaller study of 4 CMVseroconverted D+/R− LTR demonstrated similar to slightly higher frequencies of CMV-specific CD8 + T cells in the BAL compared to the peripheral blood (15). It is therefore likely that QuantiFERON ® -CMV responses in the blood can be used as a surrogate marker of CMV immunity in the lung allograft, although this will need to be formally analyzed in future studies.…”
Section: The Quantiferonmentioning
confidence: 86%
“…We have also demonstrated that CMV-specific CD8 + T cells in the BAL were no more differentiated than those in the blood, suggesting that activated CD8 + T cells were not being redistributed to and sequestered at the site of active infection. Similarly, McDyer and colleagues in a smaller study of 4 CMVseroconverted D+/R− LTR demonstrated similar to slightly higher frequencies of CMV-specific CD8 + T cells in the BAL compared to the peripheral blood (15). It is therefore likely that QuantiFERON ® -CMV responses in the blood can be used as a surrogate marker of CMV immunity in the lung allograft, although this will need to be formally analyzed in future studies.…”
Section: The Quantiferonmentioning
confidence: 86%
“…In addition, high-risk lung transplant recipients mismatched for CMV serologic status (donor positive/recipient negative; D ϩ R Ϫ ) have an increased risk for 1-yr mortality according to recent data from the International Society of Heart and Lung Transplant registry (3). It is possible that some of the differences among studies examining whether CMV infection or donor/recipient CMV serologic mismatching is a risk factor for BOS may be due to heterogeneity in CMV-specific immunity, particularly among high-risk individuals as recent data suggest (16). Thus, active CMV infection may be important as a cofactor in OB/BOS development in individuals unable to adequately control virus due to an inability to develop and/or maintain protective antiviral immunity.…”
Section: Pathogenesis Of Human Obmentioning
confidence: 99%
“…Analyses of virus-specific T-cell responses in renal transplant recipients demonstrated the presence of dominant CD8 ϩ T-cell responses that may limit viremia and protect against HCMV disease (209,213,238). In lung transplant recipients, the acquisition of HCMV-specific CD8 ϩ T-cell immunity, in addition to CD4 ϩ T-cell immunity, was associated with both freedom from HCMV disease and the preservation of allograft function compared with those who failed to develop HCMV immunity (240). Furthermore, in a study involving heart and lung transplant recipients, high frequencies of IE-1-specific CD8 ϩ T cells were shown to correlate with protection from HCMV disease (37).…”
Section: Adaptive Immunitymentioning
confidence: 99%